Assessment of the environmental behavior of pollutants in solid waste mining metallurgical (rsmm) by the method of sequential extractions and implementation of mobility models and transport - Sinche González, María (2007)
Mining activity in its different stages and operations generates considerable amount of waste material in waste rock dumps and tailings dams. They are characterized by their high metal contents, lower pH and insignifi cant amounts of organic matter. For a correct management of these wastes, in our case neutralization sludge’s and fl otation tails, its necessary to use evaluation mechanisms that help to predict the potential risk of contamination of environment, that is the main reason why the present work was developed: The fi rst part concerns sequential chemical extraction where speciation is evaluated and the kinetics of leaching to predict the time and the mobility of chosen elements. Both provide information about the availability of metals in certain environmental conditions.